Image of relief organizations for displaced Iraqis - Al Jubori, Irada Zaydan; Named, Khodhr Alyaas (ALBAHITH ALALAMI, 2018)
This research aims to know the intellectual picture the displaced people formed about aid organizations and determine whether they were positive or negative, the researchers used survey tool as standard to study the society represented by displaced people living in Baghdad camps from Shiites, Sunnis, Shabak, Turkmen, Christians, and Ezidis. The researcher reached to important results and the most important thing he found is that displaced people living in camps included in this survey hold a positive opinion about organizations working to meet their demands but they complain about the shortfall in the health care side. The research also found that displaced people from (Shabak, Turkmen, and Ezidi) minorities see that international organizations are taking care of them more than the Iraqi ones, while the Shite and Sunni displaced people said that the Iraqi organizations were providing their needs more than other organizations and this reveal that the international organizations were paying more intention for minorities .